Mini‐Open Versus Open Transforaminal Lumbar Interbody Fusion in Patients Aged ≥ 75 Years: Perioperative Surgical Burden and Clinical Outcomes - Zhendong Huang; Kelv Shen; Fengxian Jiang; Fengyu Ma; Xiang Wang; Hui Wang; Zhengfeng Lu (Orthopaedic Surgery, 2026)
ABSTRACT Purpose Patients aged ≥ 75 years are at increased risk of perioperative stress and delayed early recovery after lumbar fusion, making the choice of surgical approach clinically relevant. However, direct comparative data on mini‐open transforaminal lumbar interbody fusion (MO‐TLIF) and conventional open TLIF in this population remain limited. This study compared perioperative surgical burden, postoperative pain and functional recovery trajectories, and 12‐month radiographic fusion and satisfaction between MO‐TLIF and conventional open TLIF in patients aged ≥ 75 years. Methods This prospective cohort study included 172 patients aged ≥ 75 years with degenerative lumbar disease who underwent MO‐TLIF ( n = 84) or open TLIF ( n = 88). Eligible patients considered suitable for both procedures were alternately assigned to the MO‐TLIF or open TLIF group according to the order of enrollment. Perioperative variables included operative time, blood loss, time to first ambulation, length of stay, and complications. Laboratory markers on postoperative day (POD) 3 were assessed to reflect muscle injury and inflammatory response. Patient‐reported outcomes were assessed preoperatively and at POD 5, 1 month, 3 months, and 6 months using VAS (leg and back pain), Japanese Orthopaedic Association (JOA) score, and Oswestry Disability Index (ODI). Radiographic fusion at 12 months was graded using the Bridwell classification, and satisfaction at 12 months was evaluated with the modified MacNab criteria. Results Baseline characteristics were comparable between groups. Compared with open TLIF, MO‐TLIF was associated with shorter operative time (106.49 ± 21.69 vs. 129.40 ± 26.13 min; p < 0.001), less blood loss (104.00 ± 21.97 vs. 149.97 ± 37.12 mL; p < 0.001), earlier ambulation (2.18 ± 0.39 vs. 2.82 ± 0.56 days; p < 0.001), and shorter length of stay (9.27 ± 1.88 vs. 11.40 ± 2.31 days; p < 0.001). On POD 3, CK was lower after MO‐TLIF (274.83 ± 119.09 vs. 363.50 ± 104.72 U/L; p < 0.001), while CRP and white blood cell count were similar ( p > 0.05). PROMs improved over time in both groups; MO‐TLIF showed faster early recovery, with significantly better pain and functional scores at POD 5 or 1 month (all p < 0.05), whereas between‐group differences were not significant at 3 and 6 months ( p > 0.05). At 12 months, Bridwell fusion grades and modified MacNab satisfaction were comparable between groups ( p > 0.05). Conclusions In patients aged ≥ 75 years, both MO‐TLIF and open TLIF provided sustained pain relief and functional improvement. MO‐TLIF reduced perioperative burden and was associated with faster early recovery while achieving similar 12‐month radiographic fusion and patient satisfaction compared with open TLIF. Trail registration: Chinese Clinical Trial Registry: ChiCTR2500103261.